Chapter 3: Income packaging and social safety nets for low-income families with children in East Asia - Shu-Huah Wang, Julia (Edward Elgar Publishing, 2022)
The welfare regimes in East Asia are traditionally characterized as productivist, where social policies are subordinated to economic development goals. However, many studies have suggested that welfare approaches adopted by East Asian countries cannot be understood as a homogeneous regime. In this chapter, we investigate the heterogeneities of East Asian welfare systems for low-income families with school-aged children by using a model family approach based on data in 2019, with a specific focus on contrasting features of social assistance systems. We find that Taiwan and Japan adopt an inclusivist welfare model that offers relatively more generous social benefits. Korea can be described as a nominal inclusivist welfare model, where expansions in social welfare programs in the past years did not translate into similar generosity levels as Taiwan and Japan. Singapore adopts a minimalist welfare approach, which provides social benefits with a low level of generosity, and Hong Kong is in between a minimalist and inclusivist welfare approach. China is an emerging productivist model where the levels of social benefits are roughly enough to meet necessary living expenses for low-income families.